Incidence rate of Rift Valley fever exposure in humans and livestock from a longitudinal study in Northern Kenya - Muturi, Mathew; Mwatondo, Athman; Nijhof, A.M.; Nyamota, Richard; Nthiwa, D.; Roesel, Kristina; Wambua, Lillian; Akoko, James M.; Thumbi, S.M.; Bett, Bernard K. (Nature Research, 2025)
Unravelling the mechanisms of Rift Valley fever virus (RVFV) maintenance in endemic areas during interepidemic periods is critical for enhancing early detection and response. Unfortunately, data on key epidemiological parameters, such as incidence rates, which are crucial for risk assessments and designing targeted interventions, are almost nonexistent. We conducted a longitudinal study of 1,938 pastoral livestock and 814 livestock keepers in an endemic region of northern Kenya from March 2022 to May 2023 to estimate the incidence rate of RVFV exposure and determine risk factors for infection. We assessed exposure to RVFV in humans and livestock using an anti-RVF immunoglobulin enzyme-linked immunosorbent assay. RVFV incidence was calculated in livestock and humans as the number of new seroconversions over the total animal and person time at risk, respectively. An interval-censored regression model was employed to compute the baseline hazard and identify risk factors. We observed 113 new livestock infections over 805 animal-years at risk, translating to an annual livestock incidence rate of 0.14 per animal-year (95% CI: 0.12–0.17). Multivariable analysis found species, acaricide use, and period of sampling were significant factors that influence RVFV incidence in livestock. In humans, 15 RVFV seroconversions were observed over 629 person-years at risk, yielding an incidence rate of 24 per 1000 person-years (95% CI: 13–39). Age and sex were not significant predictors of RVFV human exposure. Seroconversion in livestock and humans suggests that low-level transmission between vertebrate hosts and vectors could be the primary mechanism for RVF viral persistence in endemic areas. Our findings highlight the need for routine serosurveillance and continuous public health education on RVF infection and prevention during interepidemic periods.